Analysis of the Application of Spectral Methods in the Restoration of Hard Dental Tissues by Indirect Restorations: A Literature Review - Klitynska Оксана; Roziuk Ігор (Actual Dentistry, 2026)
Introduction. The choice of indirect restorations in everyday clinical practice is largely based on the clinician’s experience and the availability of materials, while scientific data on the optical, biomechanical, and adhesive properties of the “restoration-tooth” system are accumulated separately and are rarely reflected in standardized protocols. This creates a gap between available research and real clinical practice, which negatively affects the predictability of long-term treatment outcomes. The aim of the work is to systematize current data on the spectral, biomechanical, and adhesive aspects of indirect restorations and, on this basis, to determine the prospects for their integration into a unified clinical algorithm. Materials and methods. For the literature review, scientific articles published between 2020 and 2025 and indexed in the PubMed and Scopus databases were selected. The search strategy focused on the following key areas: the optical properties of hard dental tissues and restorative materials; the biomechanical behavior of indirect restorations under functional loading; spectrophotometric methods for color determination; and preparation and fixation methods, specifically dentin resealing. Presentation of the main material. It has been established that the optical properties of hard dental tissues are multifaceted: fluorescence, translucency, and metamerism interact and cannot be properly assessed without instrumental spectrophotometric measurements. Furthermore, measurement conditions, particularly the degree of tooth moisture, can significantly affect the outcomes, highlighting the need for clinical protocol standardization. Analysis of biomechanical studies demonstrated that design solutions regarding cuspal overlap and the choice of the adhesive protocol directly determine stress distribution within the system and the restoration’s functional load resistance. The combination of rational preparation with the deep margin elevation technique and immediate dentin sealing was found to be highly effective in protecting residual tissues. The immediate dentin sealing protocol is confirmed to be a significant factor in reducing the incidence of postoperative complications and improving adhesive bond quality by protecting the prepared surface from contamination during the interim clinical period. Ultimately, indirect restorations demonstrate clear advantages over direct restorations in terms of biomechanical and adhesive parameters, and spectrophotometric control is a mandatory, rather than optional, component of the clinical protocol. Conclusions. Currently, no modern material can completely replicate natural tooth tissues, making instrumental color verification a mandatory component of clinical practice. To ensure the predictability of indirect restorations, three critical factors must be considered: optical parameters, biomechanical strength, and the quality of adhesive fixation. At the same time, it has been scientifically proven that the best results are achieved by combining rational tooth preparation with immediate dentin sealing before final cementation.